Global warming mode of atmospheric circulation - Zhu, Jinhong; Wang, Shaowu; Zhang, Xiangdong (Atmospheric Science Letters, 2002)
Variations of global-mean atmospheric circulation are studied using the National Center of Environment Prediction/National Center of Atmosphere (NCEP/NCAR) reanalysis data set from January 1948 to February 2001 and CCM3.6 (Community Climate Model Version 3.6) simulations for the period 1990-1999. Empirical orthogonal function (EOF) analysis indicates that variations of zonal-mean geopotential height in the tropics are usually opposite to those over the subpolar zone in both hemispheres. The first mode of EOF analysis shows that height is higher than normal in the tropics when it is lower over the subpolar zone in both hemispheres with much stronger westerlies over mid latitudes in both hemispheres, and vice versa. This mode explains about 50% variance and is predominant in the troposphere. The time series of EOF1 has a sharp transition near about 1977 and the polarity changes from negative to positive. This mode is closely related to the variations of global mean surface air temperature. The detrended correlation coefficient between EOF1 time series and the surface air temperature is 0.74 in the boreal winter. Furthermore, the lowest correlation coefficient among the other three seasons, annual mean, seasonal mean and monthly mean is higher than 0.42 which indicate the fairly good relationship between this mode and the surface air temperature. The result has been verified using CCM3.6 simulations. (C) Royal Meteorological Society Geochemistry & Geophysics Meteorology & Atmospheric Sciences SCI(E) 1 ARTICLE 1 1-13 3